Lifestyle and dietary factors in the prevention of lethal prostate cancer - Wilson, Kathryn M (Nature Publishing Group, 2012)
The prevention of lethal prostate cancer is a critical public health challenge that would improve health and reduce suffering from this disease. In this review, we discuss the evidence surrounding specific lifestyle and dietary factors in the prevention of lethal prostate cancer. We present a summary of evidence for the following selected behavioral risk factors: obesity and weight change, physical activity, smoking, antioxidant intake, vitamin D and calcium, and coffee intake.